Análise dos efeitos indiretos da exposição parenteral a antígenos tolerados na fibrose pulmonar - Evelin Nildiane da Silva Edlin (2016)
Oral tolerance, in immunology, refers to the inhibition of imune responses to proteins previously contacted by oral route. However, there are activated lymphocytes in tolerant animals after antigen ingestion and, upon parenteral immunization with a previously ingested protein, imune responses to unrelated proteins concomitantly injected are also inhibited. We labeled this phenomenon as “indirect effects of oral tolerance”. Attempts to immunize with a tolerated protein are able to block the inflammation evoked by carageenan injection in the foot-pads; drastically reduces the size and cellularity of granulomas in the lungs of noninfected mice injected with Schistoma mansoni eggs; and is able to reduce the inflammation and the fibrosis during the healing of skin wounds. Idiopathic pulmonar fibrosis in humans is characterized by a large deposition of extracellular matrix in the intersticial lung tissue leading the loss of pulmonary function. Bleomycin sulfate is an antibiotic/anti-neoplastic drug that has pulmonar fibrosis as its main side effect . Experimental models of idiopathic pulmonar fibrosis suggest that an inflammatory phase precedes the fibrosis. Our experiments aim to verify whether the indirect effects of the exposure to a tolerated antigen (ovalbumin - OVA) was able to block the inflammation and the pulmonary fibrosis induced by bleomycin. Adult male C57BL/6 mice were divided into four groups, named: control (instilled with saline); bleomycin (instilled with bleomycin); imune (injected with OVA and instilled with bleomycin) and tolerant-bleomycin (previously made tolerant to Ova, injected with OVA and instilled with bleomycin). Total and differential counting of leukocytes in bronchoalveolar lavage fluid and histologic analyses of the lungs were done 7 and 21 days after the treatments. Serum was collected 21 days after the treatment for assay of anti-Ova antibodies, to confirm the induction of tolerance in the experimental group. Lung fibrosis was evaluated at 7 and 21 days using a modified Aschoff scale. There was no difference in average weights of the animals at the end of the experiment, but the tolerant animals recovered weight faster than those in the bleomycin-treated control groups. There was no difference in the degree of pulmonar fibrosis among the groups. There was an increase in the number of leukocytes in the lavage fluid of animals treated with bleomycin, but not in the other groups (“imune” and “tolerant”). The histopathology suggested more severe and dense inflammation in the animals treated only with bleomycin than in the tolerant group. Thus, our result indicate that the exposure to the tolerated antigen (OVA) was able to reduce the inflammation, but not the fibrosis induced by bleomycin and, therefore, that inflammation is probably not a necessary step for the development of ibrosis.